A God of Justice and Reconciliation? : Perspectives from the New Testament - Punt, Jeremia (Stellenbosch Theological Journal, 2024)
Justice and reconciliation are central concepts in the NT, in explicit and implicit ways, and the terms and their usage often betray their Jewish origins and setting. As the ultimate author of justice and reconciliation, God also expects as much from God’s followers, and ultimately from and towards the cosmos. Mindful that their encompassing reach may lead to semantic inflation, justice, and reconciliation in themselves – but particularly as divine attributes – need to be plotted over a broader spectrum that may have been the case in the past, and with much more attention to these notions in their particular first century context.